Effect of the flavonoid rutin on the biology of Spodoptera frugiperda (Lepidoptera: Noctuidae) - Talita Roberta Ferreira Borges Silva; André Cirilo de Sousa Almeida; Tony de Lima Moura; Anderson Rodrigo da Silva; Silvia de Sousa Freitas; Flávio Gonçalves Jesus (Acta Scientiarum. Agronomy, 2016)
The fall armyworm Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae) is a major pest of maize crops in Brazil. The effects of plant metabolites on the biology and behavior of insects is little studied. The aim of the study was to evaluate the activity of rutin on the biology of the S. frugiperda by using artificial diets containing rutin. The study evaluated four treatments: regular diet (control group) and diets containing 1.0, 2.0 and 3.0 mg g-1 of rutin. The following biological variables parameters of the larvae were evaluated daily: development time (days), larval and pupal weight (g) and viability (%), adult longevity and total life cycle (days). A completely randomized experimental design was used with 25 replication. The rutin flavonoid negatively affected the biology of S. frugiperda by prolonging the larval development time, reducing the weight of larvae and pupae and decreasing the viability of the pupae. The addition of different concentrations of rutin prolonged the S. frugiperda life cycle. The use of plant with insecticidal activity has the potential with strategy in IPM.